Gambaran Populasi Golongan Darah Subgroup A (A1, A2) di PMI Kulon Progo - Hieronymus Rayi Prasetya; Bambang Heru Budianto; Hernayanti Hernayanti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
Subgroup A1 and A2 are the most important in the blood group A. Subgroup A1 has the A antigen more than A2 subgroup, the A2 subgroup can cause misidentification of blood group due to poor A antigen and genetic variation possessed. Misidentification of the blood group will increase the risk of transfusion reactions. This research aims to describe the A1 and A2 subgroup population in Kulon Progo district. This study was conducted with a cross sectional sampling technique. The sample in this study were taken from donors of blood group A in Kulon Progo Red Cross. Identification of A1 and A2 subgroup is done by using lectin (Dolichos biflorus extract). The result of the examination of 53 samples showed that 96,2% was A1 subgroup and 3,8% was A2 subgroup.Key words : Subgroup A1, Subgroup A2, Population, Kulon Progo